GdX/UBL4A null mice exhibit mild kyphosis and scoliosis accompanied by dysregulation of osteoblastogenesis and chondrogenesis. (20th February 2018) - Liang, Jiao; Li, Jun; Fu, Yanxia; Ren, Fangli; Xu, Jiake; Zhou, Mengyu; Li, Peiyu; Feng, Haotian; Wang, Yinyin
Abstract : GdX, also named ubiquitin‐like protein 4A, is a ubiquitin‐domain protein characterized by a ubiquitin‐like domain that regulates the movement of misfolded proteins from the endoplasmic reticulum membrane to proteasome. However, its function in skeletal biology remains unclear. Here, we report that GdX plays a crucial role in skeletal development as mice lacking GdX exhibit skeletal dysplasias, mild kyphosis, and scoliosis. During embryonic stage, GdX knockout mice display decreased bone mineral density and trabecular bone accompanied by delayed osteogenic formation. GdX knockout mice also have blended spine and small body size. At the molecular level, GdX knockout mice showed perturbed expression of osteogenesis‐related genes and cartilage developmental genes, indicative of altered differentiation of mesenchymal cell lineage. Collectively, our results uncovered GdX as a novel regulator in bone development and a potential candidate gene for skeletal dysplasias.